Identification and characterization of single nucleotide polymorphism markers in FADS2 gene associated with olive oil fatty acids composition - Ayed, Rayda Ben (Lipids Health Dis, 2017)
BACKGROUND: Genotyping of the FAD2.1 and FAD2.3 polymorphisms in the fatty acid desaturase 2 gene (FADS2) shows that they are associated with the fatty acids composition of olive oil samples. However, these associations require further confirmation in the Tunisian olive oil cultivars, and little is known about the effect of polymorphisms in fatty acid-related genes on olive oil mono- and poly- unsaturated fatty acids distribution. METHODS: A set of olive oils from 12 Tunisian cultivars was chosen. The fatty acid composition of each olive oil sample was determined by gas chromatography. Statistical and modeling Bayesian analyses were used to assess whether the FAD2.1 and FAD2.3 genotypes were associated with fatty acids composition. RESULTS: The TT-FAD2.1 and the GG-FAD2.3 genotypes were found to be associated with a lower proportion of oleic acid (C18:1) (r = −0.778, p = 0.003; r = −0.781, p= 0.003) as well as higher proportion of linoleic (C18:2) (r = 0.693, p = 0.012; r = −0.759, p= 0.004) and palmitic acids (C16:0) (r = 0.643, p = 0.024; r = −0.503, p= 0.095), making varieties with this haplotype (i.e. Chemlali Sfax and Meski) producing more saturated (C16: 0) and polyunsaturated acids than oleic acid. The latter plays a major role in preventing several diseases. CONCLUSION: The two associations FADS2 FAD2.1 and FADS2 FAD2.3 with the fatty acid compositions of olive oil samples were identified among the studied olive cultivars. These associations differed between studied cultivars, which might explain variability in lipidic composition among them and consequently reflecting genetic diversity through differences in gene expression and biochemical pathways. FADS2 locus would constitute thus a good marker for detecting interesting lipidic chemotypes among commercial olive oils.